ANALISIS KINERJA BADAN LINGKUNGAN HIDUP PROVINSI JAWA TENGAH (STUDI PENGAMATAN DI BIDANG PENGENDALIAN PENCEMARAN LINGKUNGAN HIDUP) - Eka Yulia Rahmawati Ningsih; Maesaroh Maesaroh; Hesti Lestari; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Central Java Environmental Agency was formed with the aim to develop cooperation, strengthen institutional and self-reliance of society for handling pollution and/or environmental damages and biodiversity preservation. This research analyzed central java environmental agency (Observational Study in the Field of Environmental Pollution Control Department). The PERFORMANCE Seen through three dimensions including : service quality, the need for supervision, and responsiveness using qualitative descriptive approach. The data collection techniques used in this research are observation, interviews, documentation, and Library Studies with informants from Central Java Environmental Agency (environmental pollution control Department) Based on the research indicated that performance of Central Java Environmental Agency (Observational study in the Field of Environmental pollution control department) is not optimal, because researcher found some obstacles seen on the Performance dimensions such Human Resources causing unoptimal supervision and ignorance about programs owned by Central Java Environmental Agency, while participation of society is very important to achieve its goals. To Overcome Barriers faced by Central Java Environmental Agency, some suggestions provided to optimalize its performance such as introducing Central Java Environmental Program deeply through several approaches like updating the news about implemented programs as well as conducting trainings shown to employees, engaging society in every programs, recruiting hnrary staff, and doing Periodic Maintenance And Repairing infrastructures quality.